The Effect of Internship Experience and Psychological Capital on Student Job Readiness in Gresik Regency with Work Motivation as a Mediation Variable - Anggi, Gita Fitria; Cahyono, Hadi (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The rapid changes in the world of work require university graduates to have an optimal level of job readiness, especially in Gresik Regency. The increasingly fierce competition and mismatch between graduate competencies and industry needs make the issue of student job readiness important for learning. The main purpose of this study is to analyze the influence of internship experience and psychological capital on the work readiness of students in Gresik Regency with work motivation as a mediating variable. This study uses a quantitative approach with a survey method. Respondents were students in a questionnaire and processed using the Structural Equation Modelling-Partial Least Square (SEM-PLS) technique to test for direct and indirect effects. The results of the analysis showed that the readiness of the internship. In addition, these two variables also have a positive effect on students' work readiness. Work motivation was found to have a positive effect on job readiness and acted as a mediator linking internship experience and psychological capital to job readiness. These findings confirm that students' job readiness depends not only on practical experience during the internship but also on positive psychological conditions and work motivation. This research is expected to contribute theoretically to the development of Human Resource Management science, especially in understanding the factors that affect students' work readiness. From a practical perspective, the results of this research can be used as a reference for universities in internship programs and develop student competencies that are more in line with the needs of the industrial world.